The description of names in the Vroegmiddelnederlands Woordenboek - Schoonheim, Tanneke (Nordiske Studier i Leksikografi, 1994)
The Vroegmiddelnederlands Woordenboek (Dictionary of Early Middle Dutch) is a perioddictionary, based on historical principles, which will describe the Dutch stock of words recorded in the 13th century. In this dictionary the onomastic material is completely incorporated into the articles. By means of various examples I will show in what way the !3th-century ftrst names, surnames and geographical names are handled in the dictionary and what kind of information they add to it.